Fenomena Penggunaan Bahasa di Kota Binjai Khususnya di Jalan Teuku Imam Bonjol - Sri Kurnia Hastuti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
This study aims to find out and describe the phenomenon of language usage in the city of Binjai especially on the road Teuku Imam Bonjol. Implementation of the method is done by literature review method is by reading books, opinions of experts and related articles and methods of field research is by conducting interviews of local residents. The phenomenon of language can be divided into two types of positive phenomena and negative phenomena. Examples of positive phenomena include Indonesian language has been well developed among the public, the Indonesian language has been used in the products of foreign companies, both in the packaging, procedures of use and product information produced. Examples of negative phenomena include many deviations of Indonesian rules such as the emergence of slang, alay language, pokem language, SMS language etc. Keywords: phenomenon, language usage